Dynamics and Analysis of the China-Japan Conflict: A Study on Nuclear Waste Disposal in the Fukushima Sea - Windy Dermawan; Rosania Laoli; Fajar Nur Roudhotul Jannah (Yayasan Adra Karima Hubbi, 2024)
The conflict between China and Japan over the dumping of nuclear waste in the Fukushima Sea has become an issue discussed recently. This is because nuclear waste can trigger damage and problems to marine ecosystems and human life, so China condemned Japan's actions. This research is aimed at analyzing the causes of the conflict between China and Japan. This research was also conducted to provide an explanation of what resolutions were carried out by both parties in resolving the conflict. This research was also conducted using descriptive qualitative methods using literature study instruments. The theory used is conflict resolution theory. This theory is used because it is able to explain how to resolve the conflict that occurred between China and Japan. The results of this research analysis found that the conflict between the two countries was caused by China's disagreement with Japan's actions to dispose of nuclear waste in the Fukushima Sea. The resolution carried out was through mediation between Japan and China to reach a mutual agreement with the assistance of the WTO as a mediator. The results of resolving problems using the mediation method in this conflict lead to the Dispute Settlement Body (DSB) policy which must be obeyed by all parties.